Criminal Orders of Protection for Domestic Violence: Associated Revictimization, Mental Health, and Well-being Among Victims - Sullivan, Tami P. (Journal of interpersonal violence, 2021)
All states issue criminal protection orders (POs) with the intention of improving the lives of victims of domestic violence (DV); however, there is a dearth of research examining their impact. This study aims to examine the impact of criminal POs with different levels of restrictions on victims’ revictimization, mental health, and well-being. A cross-sectional design was used to collect data regarding two time points during one interview among a sample of 298 victims in a criminal DV case. Across the three levels of PO restrictions (limited, residential stay-away, and full no-contact), participants reported significantly reduced physical, sexual, and psychological DV; unwanted pursuit behavior; post-traumatic stress and depression symptom severity; and perceived stress and fear of revictimization. The amount of change varied between groups for revictimization variables. Full no-contact restrictions were associated with the greatest decreases in revictimization. However, findings must be interpreted with caution given the heterogeneity in victims’ experiences; some victims experienced an increase in revictimization and mental health problems and a decrease in well-being. Findings suggest that the court, through criminal POs, may be a system through which to reach victims who might not otherwise connect with services to promote safety and resilience.